A Quantitative Model to Plan Regional Health Facility Systems - Dökmeci, Vedia F. (Management Science, 1977)
This paper presents a quantitative planning model to determine the optimal characteristics (number, size and locations) of a regional health facility system. The system consists of a medical center, intermediate and local hospitals, and health centers. The quantitative model is based on the minimization of the total cost (sum of the transportation and facility costs) to the society. The optimal characteristics of the system are obtained using a heuristic method which includes both interactions of sublevel hospitals and environmental conditions as well. A numerical example is given to illustrate the computational procedure.